2019
DOI: 10.32497/jobs.v5i2.1711
|View full text |Cite
|
Sign up to set email alerts
|

Design Thinking Approaches in Development of Indonesia Higher Education Startup

Abstract: <em>The Design Thinking approach as a method of problem solving and product innovation is well known in business, management and entrepreneurship. However, various design thinking models created by individual researcher and corporations often confuse users about which model to use. This research was conducted with the aim of observing the suitability of five selected design thinking models to support the development of startups in a business incubator. The research applies qualitative descriptive method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is a human-focused, prototype-driven, and innovative design process. The advantages of Design Thinking as an approach to the product's design development are also supported by Herawan (2019). It is found that the Design Thinking process is very appropriate to be used during the early stages of product development.…”
Section: Testmentioning
confidence: 92%
“…It is a human-focused, prototype-driven, and innovative design process. The advantages of Design Thinking as an approach to the product's design development are also supported by Herawan (2019). It is found that the Design Thinking process is very appropriate to be used during the early stages of product development.…”
Section: Testmentioning
confidence: 92%
“…Problem-solving methods that have not been clearly defined are carried out by understanding the needs of users who will be involved in using the application, gathering lots of ideas in brainstorming sessions and taking a direct approach through prototyping and direct testing (Susanti et al, 2019). Design Thinking is a humancentred approach, more suitable as a frame of mind for solving problems humans face while creating products or services as a solution (Herawan, 2019). This method has five stages which, as a whole, concentrate on finding problems based on human-centred.…”
Section: Introductionmentioning
confidence: 99%